EFFICACY OF DIFFERENT ANTAGONIST AGAINST THE SCLEROTIUM ROLFSII, RHIZOCTONIA SOLANI AND FUSARIUM SOLANI - A. S. ZAPE; R. M. GADE; SINGH, RAVINDRA; V. A. DESHMUKH (The Bioscan, 2014)
Ten antagonists tested under in vitro condition, maximum inhibition in radial growth of Sclerotium rolfsii was observed with P. fluorescens (71.85%) followed by T. harzianum (65.56%), T. viride (A) (65.19%) and G. virens (A) (61.48%), it was minimum with G. virens (P) (31.11%) followed by T. koningii (34.81%), T. viride (43.33%) and T. lignorum (44.81%). All the antagonists were effective in inhibiting the mycelial growth (31.11-71.85%) and sclerotial production (49.37 - 99.46%) over control. In the Rhizoctonia solani inhibition of mycelial growth by all ten isolates ranges from 54.81 to 90.74 per cent and 73.68 to 100 per cent inhibition of sclerotial production. All the antagonists were found to be significantly effective over control in inhibiting the mycelial growth of F. solani. These antagonists inhibited 62.22 to 87.03 per cent mycelial growth of the fungus. Inhibition of radial growth of Fusarium solani was maximum with T. viride (Akola isolate), T. hamatum, T. viride (Parbhani isolate), A. niger, T. harzianum, T. koningii, P. fluorescens, G. virens (Parbhani and Akola isolate) and T. lignorum. P. fluorescens.